Untersuchung des Fließverhaltens der Magnesiumknetlegie‐rung AZ31 mit Hilfe von Schichtstauch‐ und Zugversuchen. Issue 9 (14th September 2013) - Behrens, B.‐A.; Bouguecha, A.; Huinink, T.; Peshekhodov, I.; Matthias, T.; Moritz, J.; Schrödter, J.
<x xml:space="preserve">Abstract</x> Today design of metal forming processes is often supported by numerical simulation. To obtain realistic simulation results, the used material models need accurate material parameters from the material characterization. Magnesium alloys in particular are not yet sufficiently investigated. Therefore, their material parameters are scarce in literature. Especially determination of flow curves at higher degrees of deformation represents a challenge, but is necessary in order to describe the characteristic hardening and softening, as they occur in magnesium materials at elevated temperature of forming process. In this paper, an approach for the determination of a combined hardening curve from a tensile test and a layer compression test is presented. For this purpose, the corresponding values are recorded experimentally and evaluated based on the principle of the plastic work equivalence.